Sexual identities and the media an introduction - Hilton-Morrow, Wendy; Battles, Kathleen (New York Routledge, 2015)
"Sexual Identities and the Media encourages students to examine media as a site of negotiation for how people make sense of their own and others' sexual identities. Taking a critical/cultural approach, Wendy Hilton-Morrow and Kathleen Battles weave together theory, synthesis of existing research, and original analysis of contemporary media examples in order to explore key areas of debate, including: - an historical context for contemporary GLBTQ representations; - the advantages and limitations of media visibility, including a discussion of the strengths and limitations of stereotype research and the quest for "positive" representations; - the role of consumer culture in constructing GLBTQ identities; - strategies of mainstream media resistance by GLBTQ community members, including oppositional/queer reading strategies and the production of media products by and for the GLBTQ community; - the complexities of comedy as a popular narrative device in GLBTQ portrayals; - the closet as a structuring metaphor in both GLBTQ identities and engagement with media; - media representations of GLBTQ bodies as sites of non-normative desires and gender identities. Featuring an enormous range of discussion questions and case studies--from celebrity coming-out narratives, transgender models, and slash fiction writers to Glee and Modern Family--this textbook offers a timely, informative, and demystifying introduction to this vital intersection in contemporary culture"-- Provided by publisher.
1. Introduction -- 2. Historical context -- 3. Visibility -- 4. Consumer culture -- 5. Resistance -- 6. The closet -- 7. Comedy -- 8. Bodies -- 9. Conclusion.
Includes bibliographical references and index.
Keywords: Sexual minorities in mass media